An exploration of foundation phase teachers' knowledge of handwriting in the Limpopo Province. - Kgomo, Mmetja Elsie (My University, 2015)
This study sought to explore Foundation Phase teachers’ content knowledge of Handwriting. South Africa’s Annual National Assessments and international comparative research show that learners in the Limpopo Province achieve below their national and international peers. Literature suggests that the teacher’s content knowledge is the primary resource for learners’ to learn the subject. This therefore implies that if teachers know less than what they are supposed to teach then learners cannot be expected to know more than what they are taught. This research studied six teachers in the Capricorn District. All the teachers sat for a semi-structured interview and two of them were observed teaching Handwriting. The key finding of this research was that teachers in the study possessed partial subject matter content knowledge of Handwriting and that this did not translate fully into pedagogical content knowledge. Teachers also could not integrate their knowledge of the aspects of handwriting thus undermining practices that they did have knowledge of. The research concludes that teachers need training to teach handwriting effectively.